An indirect modulation strategy of matrix converters for unbalanced input supply with reduced commutation losses. Issue 9 (2nd September 2021) - Singh, Anup Kumar; Pattnaik, Swapnajit
ABSTRACT: This article is focussed on developing a novel hybrid modulation technique for matrix converter. The concept of singular value decomposition (SVD) is utilised to synthesise the intermediate fictitious DC link voltage whereas generalised scalar pulse width modulation (GSPWM) is utilised to generate the target output voltage. SVD provides the required flexibility in selecting the switch states to improve the input power factor. In contrast, GSPWM helps in reducing the switching losses significantly by clamping the output voltage in synchronisation with the peak of the output currents. This proposed phenomenon reduces the switchings at high current which in turn, reduces the losses and improves the efficiency of the converter. The feedforward compensation used at the input side of the converter helps in achieving the balanced output currents for unbalanced input conditions. The simulation and experimental results with loss analysis render validation of the proposed technique.